Клест-еловик (Loxia curvirostra L.) в Полтавской области - Карпенко, А.В. (Вестник зоологии, 1971)
Loxia curvirostra L. in the Ukraine, except for the mountain forests of the Carpathians and Crimea is considered to be a rare bird irregularly flying in during winter. Recently in the forests of the Poltava region the flocks of L. curvirostra were observed by the author in all the seasons of a year. The birds kept to the pine stands located along the banks of the Dnieprodzerzhinsk reservoir and on its islands. Recent nestlings and older young birds were met. Nesting of L. curvirostra is supposed to be not only in the Poltava region but also in other regions of the Ukraine steppe and forest-steppe zones.